The correlation between body conception and actual body mass index among adolescents: some variables and their role - Yardimci, Hülya; Hakli, Gülperi; Çakiroğlu, Funda Pınar; Özçelik, Ayşe Özfer (Progress in Nutrition, 2016)
Summary. Objective: This study aimed to determine the relationships between adolescents’ actual body mass indices BMIs and their body image perceptions and how they vary by gender and age. Subjects and Methods: The questionnaire which has two sections includes general information about the students and the Stunkard  Figure Rating Scales. Gender and age were used as explanatory variables. The research data were analyzed using SPSS statistical software. Statistical analyses included factor analysis and Cohen’s kappa test (K) A criterion alpha level of